An emotionally loaded subject – parents experiences when CHC-nurses introduce a conversation related to their child being overweight - Fridolfsson, Marie; Olsson, Anna; Ericson, Jenny; Borneskog, Catrin; Sinclair, Catrin Borneskog (BMC public health, 2024)
Background Children with a raised BMI are a major public health challenge in the world that can cause serious consequences for children’s physical and mental health. Child health care nurses’ responsibility is to promote health and prevent ill-health in children, but because being overweight is stigmatized CHC-nurses find it difficult to talk to the parents about concerns over the children’s weight, in fear of losing their trust. Aim The purpose of this study was to describe parents’ experiences of when CHC-nurses introduce a conversation related to their child being overweight. Method This study was conducted via semi-structured interviews with nine parents and the data was analyzed using qualitative content analysis. Results The result showed that being overweight in childhood is a sensitive topic, and this is presented as four categories A hard time coping , A desire to protect the Children , Changes of Parental Perspective and Trust - a mediating factor. This is a sensitive topic for the parents, who have a hard time accepting the situation and place the blame on themselves, and the nurse’s approach and relationship with the parents is of great importance for the outcome of the conversation. Conclusions Parents seem to have another perspective on health and weight than the healthcare providers, and both parents and CHC-nurses might benefit from an increased understanding of one another’s view. Parents need to gain knowledge about how healthcare providers assess children’s growth, and the CHC-nurses need to be aware about how to be responsive to the parents and allow them time to process the information. The focus should be on healthy lifestyle choices regardless of weight.